Regulating the Black Box: A Comparative Policy Analysis of National Strategies for Governing Artificial Intelligence and Upholding Human Rights - Kouadio Koffi; Olivier Sossou; Aminatou Agounke (Journal of Social Science Utilizing Technology, 2026)
Background. The rapid development of artificial intelligence (AI) has raised significant concerns regarding its potential impacts on human rights, ethics, and governance. While AI promises advancements in efficiency and innovation, its opaque decision-making processes, often referred to as the "black box" problem, create challenges for regulators aiming to ensure transparency, fairness, and accountability. This study conducts a comparative policy analysis of national strategies for governing AI, with a particular focus on how different countries address human rights concerns within their AI regulatory frameworks. Purpose. The research aims to identify the strengths and weaknesses of existing AI governance models and propose best practices for integrating human rights principles into AI regulation. Method. Using a qualitative approach, this study analyzes AI policies from the European Union, the United States, China, and India. Results. The findings reveal significant variations in the approach to regulating AI, with the EU emphasizing transparency and ethical guidelines, while countries like China prioritize state control and surveillance. Conclusion. The study concludes that a balanced approach, which incorporates human rights safeguards alongside technological innovation, is crucial for the responsible development and deployment of AI. The paper recommends stronger international cooperation and the establishment of a global framework for AI governance.